2006
DOI: 10.1038/sj.onc.1210125
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of the two reciprocal t(4;11) fusion proteins MLL·AF4 and AF4·MLL confer resistance to apoptosis, cell cycling capacity and growth transformation

Abstract: The reciprocal chromosomal translocation t(4;11) is correlated with infant, childhood, adult and therapyrelated high-risk acute leukemia. Here, we investigated the biological effects of MLL . AF4, AF4 . MLL or the combination of both reciprocal fusion proteins in a conditional in vitro cell culture model system. Several parameters like cell growth, cell cycling capacity, apoptotic behavior and growth transformation were investigated under physiological and stress conditions. Co-transfected cells displayed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…10,11 From these data it was concluded that AF4 behaves like a protooncoprotein. Recent efforts have unravelled the function of the AF4 protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 From these data it was concluded that AF4 behaves like a protooncoprotein. Recent efforts have unravelled the function of the AF4 protein.…”
Section: Discussionmentioning
confidence: 99%
“…9 By contrast, we have demonstrated that the reciprocal AF4-MLL fusion protein causes growth transformation in murine embryonal fibroblasts. 10,11 Additionally, infection of murine hematopoietic progenitor cells (Lin À Sca1 þ ) with a low titer retrovirus coding for the AF4-MLL fusion gene led to the development of predominantly proB ALL in the transplanted mice. 12 Hence, we investigated the molecular actions of the AF4-MLL oncoprotein in a subsequent study.…”
Section: Introductionmentioning
confidence: 99%
“…The mice developed exclusively B-cell lineage neoplasias, but of a more mature phenotype than normally observed in childhood leukemia. 92 Alternatively, it has been very recently suggested that the presence of both reciprocal MLL fusion proteins (MLL-AF4 and AF4-MLL) 93 or AF4-MLL alone 94 confers biological properties known from t(4;11) leukemia, suggesting that each of the two fusion proteins contribute specific properties and, in combination, also synergistic effects to the leukemic phenotype. This reproducible but confusing in vitro and in vivo data suggest that these mouse models are missing some essential ingredients of leukemogenesis in the human embryo/fetus.…”
Section: Environmental Exposures and Delayed Infection Early In Life mentioning
confidence: 99%
“…This notion is supported by the observed changes in gene transcription after short-term expression of AF4-MLL fusion protein. 41 Of interest, different complexes seem to be formed by AF4 family members, like for example, the recently described AF5 complex which contained AF4, ENL, AF10, DOT1L, AF6, AF17 and several ELL's. 42 We have not identified AF6, AF17 or ELL1-3 in our purified complexes (data not shown), suggesting that cells are able to form different complexes by AF4 family members that exert, however, highly similar functions.…”
Section: Characterization Of the Oncogenic Af4-mll Complexmentioning
confidence: 99%